UZBEKISTAN’S FOREIGN POLICY PRIORITIES SINCE 2016: PRAGMATISM AND REGIONAL COOPERATION - Xudoyberdiyev Otabek Zafar o'g'li (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Annotation: This article examines the key priorities and strategic orientations of Uzbekistan's foreign policy in the post-2016 period, following the leadership transition after the death of President Islam Karimov and the inauguration of President Shavkat Mirziyoyev. It focuses on the shift toward pragmatic diplomacy, regional cooperation, and constructive international engagement. The article highlights how Uzbekistan has redefined its foreign policy to prioritize mutually beneficial ties with Central Asian neighbors, enhance regional security, attract foreign investment, and build multivector partnerships with global powers. By analyzing official policies, international agreements, and diplomatic initiatives, the paper provides insight into the evolving foreign policy doctrine of Uzbekistan and its impact on regional stability and global integration.